2006
DOI: 10.1158/1078-0432.ccr-05-0763
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtyping of Breast Cancer from Traditional Tumor Marker Profiles Using Parallel Clustering Methods

Abstract: Purpose: Recent small-sized genomic studies on the identification of breast cancer bioprofiles have led to profoundly dishomogeneous results.Thus, we sought to identify distinct tumor profiles with possible clinical relevance based on clusters of immunohistochemical molecular markers measured on a large, single institution, case series. Experimental Design: Tumor biological profiles were explored on 633 archival tissue samples analyzed by immunohistochemistry. Five validated markers were considered, i.e., estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 31 publications
9
54
0
Order By: Relevance
“…Differential correlation of membrane and storage Trop-2 with distinct risk parameters in breast cancer was previously shown (25). IHC analysis showed that membrane Trop-2 was marginally correlated with grade.…”
Section: Activated Akt Associates With Trop-2 and Downstream Growth Ementioning
confidence: 62%
See 2 more Smart Citations
“…Differential correlation of membrane and storage Trop-2 with distinct risk parameters in breast cancer was previously shown (25). IHC analysis showed that membrane Trop-2 was marginally correlated with grade.…”
Section: Activated Akt Associates With Trop-2 and Downstream Growth Ementioning
confidence: 62%
“…Patients were selected according to the following criteria: tumor diameter: T1, T2; absence of nodal diffusion (23,24); absence of distant metastases at diagnosis. Clinical and pathologic status, tumor histotype, histologic grade, levels of expression of estrogen receptor a and progesterone receptor (PGR), and fraction of proliferating cells (% Ki-67) were recorded (25). Tumor samples were analyzed for correlated expression of Trop-2, AKT, and TP53 (26,27) …”
Section: Tumor Patient Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have been carried out investigating the application of protein biomarker panels (with known relevance to breast cancer), to large numbers of cases using tissue microarrays, exploring the existence and clinical significance of distinct breast cancer classes [13][14][15][16]. In particular, Abd El-Rehim et al [46] identified and characterised five breast cancer classes, with a sixth group of only four cases also identified but considered too small for further detailed assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an alternative approach to gene expression profiling is to use established robust laboratory technology, such as immunocytochemistry on formalin fixed paraffin embedded patient tumour samples. We and others have applied protein biomarker panels, with known relevance to breast cancer, to large numbers of cases using tissue microarrays, exploring the existence and clinical significance of distinct breast cancer classes through clustering approaches [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%